Designing Web-Based Online Mading Application - Winarsih; Sutikman (Institute of Computer Science (IOCS), 2022)
The development of online magazine information technology in Indonesia has made a lot of progress, this has also been followed by technological developments in reducing paper use. Developments in the dissemination of event information have had a good impact on event organizers because by using e-mading information media, it is easier for people to find event information. Speed ​​in obtaining easy information is one of the main requirements for obtaining information. A web-based online magazine information system is an option that is expected to help people find it easier to find information about an event they want.